Effects of different rearing technologies on production traits, water and sediment quality in European catfish (Silurus glanis) farming - Nagy, Zoltán; Gál, Dénes; Hancz, Csaba; Biró, Janka (Acta Agraria Kaposváriensis, 2020)
Aim of the study was to investigate the effect of two different rearing technologies (monoculture (M), intensive-extensive pond system (I-E)) on the production traits, water and sediment quality in case of European catfish. During a 153 days long trial two years old European catfish (mean individual weight of 485.7±3.4 g) and common carp (mean individual weight of 348.9±2.5 g) were stocked into the experimental system. Final mean weight of the fish were as follows: 1932.9±194.5 g (European catfish) and 2266.9±87.56 g (common carp). No significant differences were observed in the production traits. Specific growth rate (SGR) was lower (0.9±0.1 %/day) than expected. Significant differences were found in nitrate-N, nitrite-N, orthophosphate and total suspended solids content. Significant decrease was observed in the Kjeldahl-N and phosphate content of sediment in the extensive-intensive combined system. These results suggest that transformation of the nutrients in the combined system exceeds that of monoculture; significant amount of organic N and P compounds were removed and accumulated in the additional common carp yield.